Suitability evaluation for land reclamation in mining areas: Gol-e-Gohar Iron Ore Mine of Sirjan, Kerman, Iran. Issue 1 (2nd January 2017) - Moosavirad, S. M.; Behnia, B.
Abstract: Suitability evaluation plays an important role in the land reclamation. This paper deeply elaborates the goal of land reclamation of Gol-e-Gohar Iron Ore Mine and the principles of suitability evaluation. This was divided into four evaluation units that were assessed, respectively, by selecting evaluation factors. According to the destruction forecast, the destroyed land includes four parts: open-pit slope, open-pit bottom, dump slope and the land for roads. We developed an improved method, i.e. limit comprehensive conditions method, based on the current research achievements. The results show that the proposed method is more applicable and easier to handle.